NeMe - (:unkn) unknown (My University, 2026)
NeMe (/ˈniːm/) is a non profit, Cyprus registered cultural NGO founded in November 2004. NeMe focuses on contemporary theories and their intersection with the arts. With one of its major interests on new media technologies, NeMe introduced a number of new media art genres to the Cypriot audience including: The first funding for the production of video art in 2006 The first VJ event performed in 2008 The second video exhibition and the first in Limassol in 2008 The first totally interactive exhibition in 2015 The first live coding in 2015 The first locative media exhibition in 2017 NeMe’s virtual platform resides in two websites: www.neme.org forum.neme.org